2020
DOI: 10.1186/s12872-020-01474-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous use of metformin on kidney function in diabetes patients with acute myocardial infarction undergoing primary percutaneous coronary intervention

Abstract: Background: Diabetes patients presenting with ST-segment elevation myocardial infarction (STEMI) scheduled for primary percutaneous coronary intervention (PCI) have an increased risk of contrast induced-acute kidney injury (CI-AKI). The effects of continuous use of metformin on kidney function are still controversial in patients submitted to primary PCI. This study aimed to assess continuous metformin therapy on kidney function in diabetic patients undergoing coronary intervention. Methods: Two hundred eighty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 50 publications
0
13
0
1
Order By: Relevance
“…Furthermore, the full texts of 74 articles were reviewed, and 21 articles that did not meet the eligibility criteria were excluded. Out of the 26 full-text articles reviewed, 7 studies were able to meet our eligibility criteria on associations between metformin and CI-AKI (Table 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. These studies comprised 2,325 individuals, with 279 new cases of CI-AKI exposed to CM.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the full texts of 74 articles were reviewed, and 21 articles that did not meet the eligibility criteria were excluded. Out of the 26 full-text articles reviewed, 7 studies were able to meet our eligibility criteria on associations between metformin and CI-AKI (Table 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. These studies comprised 2,325 individuals, with 279 new cases of CI-AKI exposed to CM.…”
Section: Resultsmentioning
confidence: 99%
“…Проведенное исследование продемонстрировало, что применение метформина до госпитализации не сопровождалось увеличением риска развития ОПП после проведения ангиографии: ОР 0,85 (0,37–1,96), p=0,691. Полученный результат согласуется с недавними публикациями других авторов [ 18 ]. Во-вторых, применение метформина за пределами первых 48 ч после ЧКВ не сопровождалось повышением уровня лактата и клинически значимыми изменениями показателей pH и BE.…”
Section: Discussionunclassified
“…A prespecified analysis from the GIPS-III trial, which randomized non-diabetic patients without renal impairment presenting with ST elevation myocardial infarction to metformin or placebo early after primary PCI [30], did not show any increase in the risk of CA-AKI with metformin [12]. Similarly, other observational and randomized studies focused on diabetic patients without severe renal impairment showed that metformin continuation before and after angiography is not associated with higher risk of CA-AKI or M-ALA as compared with metformin discontinuation [9,31]. Most of the available evidence, however, is affected by several bias or potential confounders.…”
Section: Glycemic Control and Adverse Events In Patients Undergoing C...mentioning
confidence: 95%